Silver-based material and preparation method thereof, cathode assembly and plasma generator
The silver-based material is prepared by chemical composite precipitation method and two-step reduction method. Combined with thermal isostatic sintering and forging processes, the problems of poor dispersion and ablation of silver-based material are solved, and the resistance to ablation and mechanical properties are improved, and the resistance to ablation and mechanical properties are extended. The cathode assembly life is achieved and industrial production is achieved.
Patent Information
- Application Number
- CN202411416415.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The metal oxide dispersion and ablation problems of existing silver-based materials lead to a short service life of the plasma generator cathode assembly, affecting the continuity and reliability of the equipment.
The silver-based material is prepared by chemical composite precipitation method and two-step reduction method. By adding tin, indium and zinc, the pH value and flocculation precipitation process are controlled, and the material is improved by combining thermal isostatic sintering and forging processes. dispersibility and mechanical properties.
It significantly improves the ablation resistance and mechanical properties of silver-based materials, extends the service life of cathode components, and realizes the industrial production of silver-based materials, reducing production costs.
Smart Images

Figure CN118905239B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cathode materials for plasma generators, and in particular relates to a silver-based material and a preparation method thereof, a cathode assembly and a plasma generator. Background Art
[0002] In recent years, plasma ignition systems have been widely used in boiler ignition of thermal power plants. Relying on the arc generated by the plasma generator to fully burn coal powder, it has obvious advantages such as energy saving and high efficiency, high reliability, and stable operation. It has gradually replaced the traditional oil gun ignition technology. The plasma generator is the core device of the plasma ignition system, which mainly includes an anode assembly, a cathode assembly and a coil assembly, which are assembled together through a support bracket. The design life of a plasma generator is usually 5-8 years, among which the service life of the coil assembly is 5 years, the service life of the anode assembly is about 500 hours, and the service life of the cathode assembly is only 50-100 hours. Relatively speaking, the service life of the cathode assembly is much lower than that of the coil assembly and the anode assembly. This is because the cathode assembly not only undertakes the task of emitting electrons, but also withstands the high-energy bombardment of charged particles of arc plasma, which will cause the temperature of the working area of the cathode assembly to rise, all of which lead to the short service life and poor stability of the cathode assembly. Affected by the service life of the cathode assembly, the plasma generator will frequently replace the cathode assembly during operation, which seriously affects the continuity, stability and reliability of the generator set. Therefore, designing and developing a long-lasting, high-quality cathode assembly is very urgent for the use of plasma generators.
[0003] Usually, the cathode material used in cathode components is mainly high-conductivity silver. Silver has good electrical and thermal conductivity and is often processed into core components of electrical power equipment. However, silver as a cathode material also has the problems of short service life and easy ablation. Studies have found that the fundamental reason is that silver has a large electron work function and weak electron emission ability, which causes the temperature of the cathode component to be too high during operation. Silver has a low melting point and low hardness, and is prone to ablation at high temperatures. This shows that there are great limitations in using pure silver as a cathode material.
[0004] The Chinese patent application with publication number CN101497128A discloses a method for preparing a high-performance cathode material for plasma ignition. The cathode material is prepared by ball milling and plasma sintering with silver and rare earth oxide as raw materials. The obtained material has high density, good electrical conductivity, strong electron emission ability and improved service life. The cathode material preparation method disclosed in the master's thesis "Preparation and Experimental Research of High-Performance Cathode Materials in Plasma Ignition Devices of Thermal Power Plants" of North China Electric Power University is similar to the above-mentioned Chinese patent application. These prior art solutions introduce rare earth oxides into silver-based materials to achieve the purpose of extending the service life of cathode components. This is because the metal oxides have a high melting point and stable performance, have excellent thermal electron emission ability, and can reduce the work function of electrons in the material. However, the rare earth oxides in the cathode materials obtained by these prior art solutions are not dispersed enough, and are mainly distributed around the silver particles, resulting in weak electron emission dispersion ability, and limited effect in overcoming the ablation problem and extending the life of the material. In addition, the discharge plasma technology is not suitable for mass industrial production at present, and the production cost is relatively high. Summary of the invention
[0005] The purpose of the present invention is to provide a silver-based material and a preparation method thereof, a cathode assembly and a plasma generator, which solve the problems of poor dispersion and easy ablation of metal oxides in existing silver-based materials, and realize the mass production of silver-based materials for cathode assemblies of long-lasting and high-performance plasma generators.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for preparing a silver-based material comprises the following steps:
[0008] S1, adding silver nitrate, tin acetate, indium salt and zinc salt into water, stirring and mixing to obtain a metal salt solution; adding sodium hydroxide solution into the metal salt solution until the pH value of the metal salt solution reaches 9-11, thereby obtaining a suspension;
[0009] S2, adding polyacrylamide to the suspension to perform flocculation precipitation treatment, and washing and drying the obtained precipitate to obtain a composite precipitate;
[0010] S3, in a reducing atmosphere, heating the composite precipitate to 100-150° C., keeping the temperature for a first preset time, and then heating the composite precipitate to 250-300° C., keeping the temperature for a second preset time, to obtain a multi-component composite metal oxide silver composite powder;
[0011] S4, hot isostatic pressing and sintering the multi-component composite metal oxide silver composite powder to obtain a silver-based material coarse material;
[0012] S5, hot forging the silver-based material raw material into a shape to obtain the silver-based material.
[0013] Preferably, in S1, the indium salt is indium nitrate, indium sulfate or indium trichloride, and the zinc salt is zinc nitrate, zinc sulfate or zinc chloride.
[0014] Preferably, in S1, the molar ratio of silver ions, tin ions, indium ions and zinc ions in the metal salt solution is 1: (0.071-0.077): (0.0038-0.0098): (0.019-0.030).
[0015] Preferably, in S2, the added amount of the polyacrylamide is 0.08%-0.1% of the sum of the mass of silver nitrate, tin acetate, indium salt and zinc salt.
[0016] Preferably, in S3, the first preset time is 1-2 hours, and the second preset time is 1-2 hours.
[0017] Preferably, S4 specifically includes:
[0018] S41, compacting the multi-component composite metal oxide silver composite powder, and then pressing it into a rough material at a pressure of 200-300 MPa;
[0019] S42, under a pressure of 50-100 MPa, the raw material is heated to 250-300°C for preheating, and then heated to 800-900°C for hot isostatic pressing sintering.
[0020] Preferably, S5 specifically includes:
[0021] S51, in a reducing atmosphere, heating the silver-based material raw material to 500-700°C for preheating for 20-30 minutes, and then forging, with a forging amount of 10%-20% and a forging time of 20-30 seconds;
[0022] S52, after forging, heat to 500-700℃ for preheating for 10-15min, and then forge, the forging amount is 10%-15%, and the forging time is 20-30s;
[0023] S53, repeat S52 several times to obtain a silver-based material.
[0024] The present invention also provides a silver-based material obtained by the preparation method as described above.
[0025] The present invention also provides a cathode assembly, wherein the material of the cathode assembly is the silver-based material as described above.
[0026] The present invention also provides a plasma generator, comprising the cathode assembly as described above.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention uses a variety of metal salts as precursors, and prepares a silver-based material with small particle size, light particle agglomeration, and uniform distribution of multi-component composite metal oxides through chemical composite precipitation and two-step reduction. First, the present invention adds metal tin, indium and zinc with small electron work function and strong thermal electron emission ability to the silver-based material, and the multi-component composite metal oxides formed by tin, indium and zinc play a synergistic role in matching each other, thereby improving the life of the material as a cathode component of the plasma generator. Secondly, the present invention adds sodium hydroxide solution to the metal salt solution until the pH value of the metal salt solution is 9-11, obtains a suspension by controlling the pH value, and adds polyacrylamide to the suspension for flocculation and precipitation treatment; relative to the direct precipitation method, the multi-component composite metal oxide silver composite powder obtained by the flocculation and precipitation method of the present invention has a smaller particle size, which can improve the dispersibility of the multi-component composite metal oxide in the silver matrix, thereby improving the electron emission dispersion ability of the silver-based material, and then improving the anti-ablation performance of the silver-based material, and extending the service life of the silver-based material. In addition, the small particle size of the multi-component composite metal oxide silver composite powder can effectively avoid grain growth during the subsequent hot isostatic pressing sintering process. Again, the present invention adopts a two-step continuous reduction method, first reducing silver oxide at low temperature, and then reducing the remaining silver oxide at high temperature. Compared with one-step reduction, the two-step continuous reduction can avoid the evaporation of silver oxide when it is directly heated to high temperature, improve the material utilization rate, and at the same time, the silver oxide can be reduced more fully, and a multi-component composite metal oxide silver composite powder with good reduction effect and stable quality is obtained, thereby improving the strength and electron emission ability of the final silver-based material, and then improving the anti-ablation performance of the silver-based material, and extending the service life of the silver-based material. In addition, compared with the traditional sintering method, the present invention adopts the hot isostatic pressing sintering method, which can improve the density of the material, thereby enhancing the mechanical properties of the material. In summary, the present invention improves the dispersibility of multi-component composite metal oxides in the silver matrix through chemical composite precipitation method and two-step reduction method, and the multi-component composite metal oxides in the obtained silver-based material are distributed and dispersed inside the silver matrix, so that the anti-ablation ability and mechanical properties of the silver-based material are significantly improved, and the present invention avoids the use of discharge plasma technology, and realizes the industrial production of silver-based materials for cathode components of long-lasting high-performance plasma generators.
[0029] Furthermore, the ratio of metal ions in the present invention is set by combining the electron emission ability and the conductivity of the material. When the content of the multi-component composite metal oxide is too high, the material density is reduced and the conductivity is reduced. Therefore, the present invention controls the addition amount of metal tin, indium and zinc within a suitable range to ensure that the final silver-based material has good conductivity.
[0030] Furthermore, the present invention also includes the operation of pressing the multi-component composite metal oxide composite powder before hot isostatic pressing sintering. Compared with directly performing hot isostatic pressing sintering, the density of the silver-based material can be effectively improved, the defect formation can be reduced, and the electron emission dispersion ability of the silver-based material can be improved, and then the ablation resistance of the silver-based material can be improved, and the service life of the silver-based material can be extended; at the same time, the serious shrinkage problem of the silver-based material after hot isostatic pressing sintering is avoided, and the utilization rate of the material after hot isostatic pressing sintering is improved.
[0031] Furthermore, the present invention can eliminate the sintering defects of the silver-based material through the forging process, and also has a shaping effect, which is convenient for one-time processing into a cathode assembly in the later stage; when the preheating temperature is too high and the preheating time is too long, there will be coarse grains of the silver matrix; when the preheating temperature is too low and the preheating time is too short, forging will cause cracks in the silver matrix. Therefore, the forging process of the present invention controls the appropriate preheating temperature and time.
[0032] In the silver-based material prepared by the present invention, the multi-component composite metal oxide is dispersed in the silver matrix, and the ablation resistance and mechanical properties of the silver-based material are significantly improved. The material can be used as a raw material for manufacturing a cathode assembly for a plasma generator, and can be used to manufacture a cathode assembly for a plasma generator. The cathode assembly based on the silver-based material of the present invention has strong ablation resistance and improved life. The cathode assembly, the anode assembly and the coil assembly can be assembled together into a plasma generator, and because the life of the cathode assembly is extended, the obtained plasma generator does not need to frequently replace the cathode assembly. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 is a flow chart of the preparation method of the silver-based material of the present invention;
[0035] Figure 2 The scanning electron microscope photograph (a) of the multi-component composite metal oxide silver composite powder obtained after reduction in step 3 of Example 2 of the present invention and the scanning electron microscope photograph (b) of the multi-component composite metal oxide silver composite powder obtained after reduction in step 3 of Comparative Example 1 of the present invention;
[0036] Figure 3The ablation morphology scanning photo (a) of the silver-based material prepared in Example 2 of the present invention after the simulated electron emission test and the ablation morphology scanning photo (b) of the silver-based material prepared in Comparative Example 1 of the present invention after the simulated electron emission test;
[0037] Figure 4 is a stress-strain curve diagram of the silver-based material in Example 2 of the present invention and Comparative Example 2;
[0038] Figure 5 The present invention relates to a scanning photo of the structure of the coarse silver-based material obtained after reduction in step 5 in Example 2 of the present invention and a photo of the coarse silver-based material coming out of the furnace (a), and a scanning photo of the structure of the coarse silver-based material obtained after reduction in step 5 in Comparative Example 3 of the present invention and a photo of the coarse silver-based material coming out of the furnace (b). DETAILED DESCRIPTION
[0039] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0040] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0041] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0042] like Figure 1 As shown, the method for preparing the silver-based material of the present invention comprises the following steps:
[0043] S1, adding silver nitrate, tin acetate, indium salt and zinc salt into water, stirring and mixing to obtain a metal salt solution; adding sodium hydroxide solution into the metal salt solution, adjusting the pH value of the metal salt solution to 9-11, and obtaining a suspension;
[0044] S2, adding polyacrylamide to the suspension to perform flocculation precipitation treatment, and washing and drying the obtained precipitate to obtain a composite precipitate;
[0045] S3, in a reducing atmosphere, heating the composite precipitate to 100-150° C., keeping the temperature for a first preset time, and then heating the composite precipitate to 250-300° C., keeping the temperature for a second preset time, to obtain a multi-component composite metal oxide silver composite powder;
[0046] S4, hot isostatic pressing and sintering the multi-component composite metal oxide silver composite powder to obtain a silver-based material coarse material;
[0047] S5, hot forging the silver-based material raw material into a shape to obtain the silver-based material.
[0048] In the present invention, the indium salt is indium nitrate, indium sulfate or indium trichloride; the zinc salt is zinc nitrate, zinc chloride or zinc sulfate.
[0049] The molar ratio of silver ions, tin ions, indium ions and zinc ions in the metal salt solution is 1: (0.071-0.077): (0.0038-0.0098): (0.019-0.030), and the ratio of water to the sum of the mass of silver nitrate, tin acetate, indium salt and zinc salt is not less than 30: 1. The amount of polyacrylamide added is 0.08%-0.1% of the sum of the mass of silver nitrate, tin acetate, indium salt and zinc salt.
[0050] In S3 of the present invention, the first preset time is 1-2 hours, and the second preset time is 1-2 hours.
[0051] In the above method of the present invention, S4 specifically includes:
[0052] S41, placing the multi-component composite metal oxide silver composite powder in a sheath mold, first vibrating it, and then pressing it into a rough material at a pressure of 200-300 MPa, wherein the density of the rough material reaches 70%-80%, and then vacuum welding and sealing it;
[0053] S42, under a pressure of 50-100 MPa, the raw material is heated to 250-300°C for preheating treatment for 1-2 hours, and then heated to 800-900°C for hot isostatic pressing sintering for 2-4 hours.
[0054] The material of the encapsulation mold used in the present invention is copper or steel, and the shape can be cylindrical, plate-shaped or rod-shaped, and the encapsulation mold has an exhaust hole structure.
[0055] In the above method of the present invention, S5 specifically includes:
[0056] S51, preheating the silver-based material rough material, and then forging it;
[0057] S52, after forging, preheating treatment is performed, and then forging is performed;
[0058] S53, repeat S52 several times to obtain a silver-based material.
[0059] Among them, the preheating treatment temperature in S51 and S52 is 500-700°C, the preheating treatment time in S51 is 20-30min, the forging amount is 10%-20%, and the forging time is 20-30s; the preheating treatment time in S52 is 10-15min, the forging amount is 10%-15%, and the forging time is 20-30s.
[0060] In the silver-based material prepared by the present invention, the multi-component composite metal oxides are dispersed in the silver matrix, and the ablation resistance and mechanical properties of the silver-based material are significantly improved. The silver-based material can be used as a raw material for manufacturing a cathode assembly for a plasma generator, and is used to manufacture a cathode assembly for a plasma generator. The cathode assembly is assembled together with an anode assembly and a coil assembly into a plasma generator.
[0061] The present invention is described in detail below with reference to specific embodiments.
[0062] Example 1
[0063] Step 1, weigh 300g of silver nitrate, 48g of tin acetate, 4g of indium nitrate and 10g of zinc nitrate, pour them into 15L of deionized water in sequence and stir them mechanically until they are evenly mixed, then pour a 2mol / L sodium hydroxide solution into the obtained metal salt solution until the pH value of the metal salt solution is 10.5 to obtain a suspension.
[0064] Step 2, weighing 0.4 g of polyacrylamide and adding it to the suspension, then mechanically stirring it for flocculation and precipitation, filtering it, washing the obtained precipitate with anhydrous ethanol for multiple times, and then drying it in an oven at 60° C. for 24 hours to obtain a composite precipitate.
[0065] Step 3, placing the composite precipitate into a continuous hydrogen reduction furnace for reduction, using two temperature zones for heating, the heating temperature of the first temperature zone is 150°C, the heating temperature of the second temperature zone is 300°C, the reduction time of each temperature zone is 1h, and after reduction, a multi-component composite metal oxide silver composite powder is obtained.
[0066] Step 4, pour the multi-component composite metal oxide silver composite powder into a plate-shaped encapsulation mold, first vibrate it, and then press it into a rough material at a pressure of 220MPa. The density of the rough material is 73%, and then vacuum weld it to seal it.
[0067] Step 5: Place the sealed encapsulation mold into the furnace of the hot isostatic pressing equipment, and then set the pressure in the cavity to 50MPa. First, perform preheating, that is, keep the temperature at 300℃ for 1h; then perform hot isostatic pressing sintering, that is, continue to heat up to 800℃ and keep the temperature for 2h; after cooling, take out the encapsulation mold to obtain the silver-based material rough material.
[0068] Step 6, placing the silver-based material raw material into a 600° C. hydrogen reduction furnace for heating for 30 minutes, and then placing it on an air hammer device for forging, with a forging time of 30 seconds and a forging amount of 20%.
[0069] Step 7, put it back into the 600℃ hydrogen reduction furnace for heating for 10min, and then put it on the air hammer equipment for forging, the forging time is 20s, and the forging amount is 15%. Repeat this step twice to obtain a plate-like silver-based material.
[0070] Example 2
[0071] Step 1, weigh 250g of silver nitrate, 40g of tin acetate, 3g of indium sulfate and 6g of zinc chloride, pour them into 10L of deionized water in sequence and stir them mechanically until they are evenly mixed, then pour a 2mol / L sodium hydroxide solution into the obtained metal salt solution until the pH value of the metal salt solution reaches 9, and then obtain a suspension.
[0072] Step 2, weighing 0.25g of polyacrylamide and adding it to the suspension, then mechanically stirring it to evenly flocculate and precipitate it, filtering it, washing the obtained precipitate with anhydrous ethanol for multiple times, and then drying it in an oven at 60°C for 24h to obtain a composite precipitate.
[0073] Step 3, placing the composite precipitate into a continuous hydrogen reduction furnace for reduction, using two temperature zones for heating, the heating temperature of the first temperature zone is 100°C, the heating temperature of the second temperature zone is 250°C, the reduction time of each temperature zone is 2h, and after reduction, a multi-component composite metal oxide silver composite powder is obtained.
[0074] Step 4, pour the multi-component composite metal oxide silver composite powder into a cylindrical encapsulation mold, first vibrate it, and then press it into a rough material at a pressure of 300MPa. The density of the rough material is 78%, and then vacuum weld it to seal it.
[0075] Step 5: Place the sealed encapsulation mold into the hot isostatic pressing equipment chamber, and then set the chamber pressure to 80 MPa. First, perform preheating, i.e., heat to 260°C and keep warm for 1.5 hours; then perform hot isostatic pressing sintering, i.e., continue to heat to 900°C and keep warm for 2.5 hours; after cooling, take out the encapsulation mold to obtain the silver-based material rough material.
[0076] Step 6, placing the silver-based material raw material into a 500° C. hydrogen reduction furnace for heating for 20 minutes, and then placing it on an air hammer device for forging, with a forging time of 25 seconds and a forging amount of 10%.
[0077] Step 7, put it back into the 500℃ hydrogen reduction furnace for heating for 10 minutes, and then put it on the air hammer equipment for forging, the forging time is 30 seconds, and the forging amount is 10%. Repeat this step three times to obtain a cylindrical silver-based material.
[0078] Example 3
[0079] Step 1, weigh 400g of silver nitrate, 60g of tin acetate, 4.8g of indium trichloride and 10g of zinc sulfate, pour them into 25L of deionized water in sequence and stir them mechanically until they are evenly mixed, then pour a 2mol / L sodium hydroxide solution into the obtained metal salt solution until the pH value of the metal salt solution is 11, and then obtain a suspension.
[0080] Step 2, weigh 0.5g of polyacrylamide and add it to the suspension, then mechanically stir it evenly for flocculation and precipitation, filter it, wash the obtained precipitate with anhydrous ethanol for multiple times, and then dry it in an oven at 60°C for 24h to obtain a composite precipitate.
[0081] Step 3, placing the composite precipitate into a continuous hydrogen reduction furnace for reduction, using two temperature zones for heating, the heating temperature of the first temperature zone is 150°C, the heating temperature of the second temperature zone is 250°C, the reduction time of each temperature zone is 1.5h, and after reduction, a multi-component composite metal oxide silver composite powder is obtained.
[0082] Step 4, pour the multi-component composite metal oxide silver composite powder into a rod-shaped encapsulation mold, first vibrate it, and then press it into a rough material at a pressure of 200MPa. The density of the rough material is 70%, and then vacuum weld it to seal it.
[0083] Step 5: Place the sealed encapsulation mold into the hot isostatic pressing equipment chamber, and then set the chamber pressure to 100 MPa. First, perform preheating, i.e., heat to 280°C and keep it for 2 hours; then perform hot isostatic pressing sintering, i.e., continue to heat to 900°C and keep it for 3 hours; after cooling, take out the encapsulation mold to obtain the silver-based material rough material.
[0084] Step 6, placing the silver-based material raw material into a 700° C. hydrogen reduction furnace for heating for 25 minutes, and then placing it on an air hammer device for forging, with a forging time of 30 seconds and a forging amount of 15%.
[0085] Step 7, put it back into the 700℃ hydrogen reduction furnace for heating for 12 minutes, and then put it on the air hammer equipment for forging, the forging time is 25 seconds, and the forging amount is 15%. Repeat this step twice to obtain a rod-shaped silver-based material.
[0086] Example 4
[0087] Step 1, weigh 350g of silver nitrate, 54g of tin acetate, 4.4g of indium sulfate and 8g of zinc chloride, pour them into 20L of deionized water in sequence and stir them mechanically until they are evenly mixed, then pour a 2mol / L sodium hydroxide solution into the obtained metal salt solution until the pH value of the metal salt solution reaches 9.5, and then obtain a suspension.
[0088] Step 2, weighing 0.45g of polyacrylamide and adding it to the suspension, then mechanically stirring it for flocculation and precipitation, filtering it, washing the obtained precipitate with anhydrous ethanol for multiple times, and then drying it in an oven at 60°C for 24h to obtain a composite precipitate.
[0089] Step 3, placing the composite precipitate into a continuous hydrogen reduction furnace for reduction, using two temperature zones for heating, the heating temperature of the first temperature zone is 120°C, the heating temperature of the second temperature zone is 260°C, the reduction time of each temperature zone is 2h, and after reduction, a multi-component composite metal oxide silver composite powder is obtained.
[0090] Step 4, pour the multi-component composite metal oxide silver composite powder into a cylindrical encapsulation mold, first vibrate it, and then press it into a rough material at a pressure of 280MPa. The density of the rough material is 80%, and then vacuum weld it to seal it.
[0091] Step 5: Place the sealed encapsulation mold into the hot isostatic pressing equipment furnace, and then set the pressure in the cavity to 60MPa. First, perform preheating, i.e., heat up to 280°C and keep it for 2 hours; then perform hot isostatic pressing sintering, i.e., continue to heat up to 860°C and keep it for 4 hours; after cooling, take out the encapsulation mold to obtain the silver-based material rough material.
[0092] Step 6, placing the silver-based material raw material into a 650° C. hydrogen reduction furnace for heating for 22 minutes, and then placing it on an air hammer device for forging, with a forging time of 25 seconds and a forging amount of 15%.
[0093] Step 7, put it back into the 650℃ hydrogen reduction furnace for heating for 15min, and then put it on the air hammer equipment for forging, the forging time is 20s, and the forging amount is 15%. Repeat this step twice to obtain a cylindrical silver-based material.
[0094] Example 5
[0095] Step 1, weigh 200g of silver nitrate, 33g of tin acetate, 2.8g of indium nitrate and 4.5g of zinc sulfate, pour them into 8L of deionized water in sequence and stir them mechanically until they are evenly mixed, then pour a 2mol / L sodium hydroxide solution into the obtained metal salt solution until the pH value of the metal salt solution is 10.5, and then obtain a suspension.
[0096] Step 2, weighing 0.2 g of polyacrylamide and adding it to the suspension, then mechanically stirring it for flocculation and precipitation, filtering it, washing the obtained precipitate with anhydrous ethanol for multiple times, and then drying it in an oven at 60° C. for 24 hours to obtain a composite precipitate.
[0097] Step 3, placing the composite precipitate into a continuous hydrogen reduction furnace for reduction, using two temperature zones for heating, the heating temperature of the first temperature zone is 140°C, the heating temperature of the second temperature zone is 260°C, the reduction time of each temperature zone is 1.5h, and after reduction, a multi-component composite metal oxide silver composite powder is obtained.
[0098] Step 4, pour the multi-component composite metal oxide silver composite powder into a plate-shaped encapsulation mold, first vibrate it, and then press it into a rough material at a pressure of 260MPa. The rough material density is 74%, and then vacuum weld and seal it.
[0099] Step 5: Place the sealed encapsulation mold into the hot isostatic pressing equipment furnace, and then set the pressure in the cavity to 60 MPa. First, perform preheating, i.e., heat to 250°C and keep warm for 1.5 hours; then perform hot isostatic pressing sintering, i.e., continue to heat to 830°C and keep warm for 2 hours; after cooling, take out the encapsulation mold to obtain the coarse material of multi-component composite metal oxide silver-based material.
[0100] Step 6, placing the silver-based material crude material into a 550° C. hydrogen reduction furnace for heating for 26 minutes, and then placing it on an air hammer device for forging, with a forging time of 30 seconds and a forging amount of 10%.
[0101] Step 7, put it back into the 550℃ hydrogen reduction furnace for heating for 15min, and then put it on the air hammer equipment for forging, the forging time is 30s, and the forging amount is 15%. Repeat this step once to obtain a plate-like silver-based material.
[0102] Comparative Example 1
[0103] Step 1, weigh 250g of silver nitrate, 40g of tin acetate, 3g of indium sulfate and 6g of zinc chloride, pour them into 10L of deionized water in sequence and stir them mechanically until they are evenly mixed, then pour a 2mol / L sodium hydroxide solution into the obtained metal salt solution until the pH value of the metal salt solution is 14 and a precipitate is precipitated.
[0104] Step 2: After filtration, the obtained precipitate is washed multiple times with anhydrous ethanol, and then dried in an oven at 60° C. for 24 hours to obtain a composite precipitate.
[0105] Step 3, placing the composite precipitate into a continuous hydrogen reduction furnace for reduction, using two temperature zones for heating, the heating temperature of the first temperature zone is 100°C, the heating temperature of the second temperature zone is 250°C, the reduction time of each temperature zone is 2h, and after reduction, a multi-component composite metal oxide silver composite powder is obtained.
[0106] Step 4, pour the multi-component composite metal oxide silver composite powder into the cylindrical plate jacket mold, first vibrate it, and then press it into a rough material at a pressure of 300MPa. The density of the rough material is 78%, and then vacuum weld it to seal it.
[0107] Step 5: Place the sealed encapsulation mold into the hot isostatic pressing equipment chamber, and then set the chamber pressure to 80 MPa. First, perform preheating, i.e., heat to 260°C and keep warm for 1.5 hours; then perform hot isostatic pressing sintering, i.e., continue to heat to 900°C and keep warm for 2.5 hours; after cooling, take out the encapsulation mold to obtain the silver-based material rough material.
[0108] Step 6, placing the silver-based material raw material into a 500° C. hydrogen reduction furnace for heating for 20 minutes, and then placing it on an air hammer device for forging, with a forging time of 25 seconds and a forging amount of 10%.
[0109] Step 7, put it back into the 500℃ hydrogen reduction furnace for heating for 10 minutes, and then forge it on the air hammer equipment, the forging time is 30 seconds, and the forging amount is 10%. Repeat this step three times to obtain a cylindrical silver-based material.
[0110] Comparative Example 2
[0111] Step 1, weigh 250g of silver nitrate, 40g of tin acetate, 3g of indium sulfate and 6g of zinc chloride, pour them into 10L of deionized water in sequence and stir them mechanically until they are evenly mixed, then pour a 2mol / L sodium hydroxide solution into the obtained metal salt solution until the pH value of the metal salt solution reaches 9, and then obtain a suspension.
[0112] Step 2, weighing 0.25g of polyacrylamide and adding it to the suspension, then mechanically stirring it to evenly flocculate and precipitate it, filtering it, washing the obtained precipitate with anhydrous ethanol for multiple times, and then drying it in an oven at 60°C for 24h to obtain a composite precipitate.
[0113] Step 3, placing the composite precipitate into a continuous hydrogen reduction furnace for reduction, the reduction temperature is 250° C., the reduction time is 4 hours, and after reduction, a multi-component composite metal oxide silver composite powder is obtained.
[0114] Step 4, pour the multi-component composite metal oxide silver composite powder into a cylindrical encapsulation mold, first vibrate it, and then press it into a rough material at a pressure of 300MPa. The density of the rough material is 78%, and then vacuum weld it to seal it.
[0115] Step 5: Place the sealed encapsulation mold into the hot isostatic pressing equipment chamber, and then set the chamber pressure to 80 MPa. First, perform preheating, i.e., heat to 260°C and keep warm for 1.5 hours; then perform hot isostatic pressing sintering, i.e., continue to heat to 900°C and keep warm for 2.5 hours; after cooling, take out the encapsulation mold to obtain the silver-based material rough material.
[0116] Step 6, placing the silver-based material raw material into a 500° C. hydrogen reduction furnace for heating for 20 minutes, and then placing it on an air hammer device for forging, with a forging time of 25 seconds and a forging amount of 10%.
[0117] Step 7, put it back into the 500℃ hydrogen reduction furnace for heating for 10 minutes, and then put it on the air hammer equipment for forging, the forging time is 30 seconds, and the forging amount is 10%. Repeat this step three times to obtain a cylindrical silver-based material.
[0118] Comparative Example 3
[0119] Step 1, weigh 250g of silver nitrate, 40g of tin acetate, 3g of indium sulfate and 6g of zinc chloride, pour them into 10L of deionized water in sequence and stir them mechanically until they are evenly mixed, then pour a 2mol / L sodium hydroxide solution into the obtained metal salt solution until the pH value of the metal salt solution reaches 9, and then obtain a suspension.
[0120] Step 2, weighing 0.25g of polyacrylamide and adding it to the suspension, then mechanically stirring it to evenly flocculate and precipitate it, filtering it, washing the obtained precipitate with anhydrous ethanol for multiple times, and then drying it in an oven at 60°C for 24h to obtain a composite precipitate.
[0121] Step 3, placing the composite precipitate into a continuous hydrogen reduction furnace for reduction, using two temperature zones for heating, the heating temperature of the first temperature zone is 100°C, the heating temperature of the second temperature zone is 250°C, the reduction time of each temperature zone is 2h, and after reduction, a multi-component composite metal oxide silver composite powder is obtained.
[0122] Step 4, pouring the multi-component composite metal oxide silver composite powder into a cylindrical encapsulation mold, vibrating it, and then vacuum welding and sealing it.
[0123] Step 5: Place the sealed encapsulation mold into the hot isostatic pressing equipment chamber, and then set the chamber pressure to 80 MPa. First, perform preheating, i.e., heat to 260°C and keep warm for 1.5 hours; then perform hot isostatic pressing sintering, i.e., continue to heat to 900°C and keep warm for 2.5 hours; after cooling, take out the encapsulation mold to obtain the silver-based material rough material.
[0124] Step 6, placing the silver-based material raw material into a 500° C. hydrogen reduction furnace for heating for 20 minutes, and then placing it on an air hammer device for forging, with a forging time of 25 seconds and a forging amount of 10%.
[0125] Step 7, put it back into the 500℃ hydrogen reduction furnace for heating for 10 minutes, and then put it on the air hammer equipment for forging, the forging time is 30 seconds, and the forging amount is 10%. Repeat this step three times to obtain a cylindrical silver-based material.
[0126] Figure 2(a) is a scanning electron microscope photo of the multi-component composite metal oxide silver composite powder obtained after reduction in step 3 of Example 2 of the present invention, and (b) is a scanning electron microscope photo of the multi-component composite metal oxide silver composite powder obtained after reduction in step 3 of Comparative Example 1 of the present invention. Figure 2 As can be seen in (a), the multi-component composite metal oxide silver composite powder is composed of a large number of uniform fine particles. Figure 2 It can be seen from (b) that the particle size of the multi-component composite metal oxide silver composite powder of Comparative Example 1 is significantly larger than that of the composite powder of Example 1. The difference between Comparative Example 1 and Example 1 is that the amount of sodium hydroxide solution added in Comparative Example 1 is increased so that the pH reaches 14 and the precipitate is directly precipitated. It can be explained that the present invention controls the pH to produce a suspension and then collects the precipitate by flocculation precipitation, thereby reducing the particle size of the multi-component composite metal oxide silver composite powder, thereby improving the dispersibility of the multi-component composite metal oxide in the silver matrix, making the multi-component composite metal oxide dispersed in the silver matrix, and thus improving the electron emission dispersion ability and ablation resistance of the silver-based material. The direct precipitation method will cause the composite powder particles to be coarse, and the increase in the particle size of the multi-component composite metal oxide silver composite powder will reduce the distribution of the multi-component composite metal oxide in the silver-based material, and ultimately reduce the electron emission dispersion ability and ablation resistance of the silver-based material.
[0127] Figure 3 (a) is a scanning photo of the ablation morphology of the silver-based material prepared in Example 2 of the present invention after the simulated electron emission test, and (b) is a scanning photo of the ablation morphology of the silver-based material prepared in Comparative Example 1 of the present invention after the simulated electron emission test. Figure 3 As can be seen in (a), the silver-based material has a smooth ablation morphology and strong electron emission dispersion ability; Figure 3 As can be seen in (b), the ablation morphology of the silver-based material is relatively rough, with obvious pits and large-sized pits. Figure 2 It can be explained that the dispersion of multi-component composite metal oxides in the silver matrix is beneficial to the electron emission dispersion ability, thereby improving the ablation resistance of the silver-based material and ultimately extending the service life of the silver-based material.
[0128] Figure 4 2 is a stress-strain curve diagram of the silver-based material obtained in Example 2 of the present invention and Comparative Example 2. Figure 3 It can be seen that the strength of the silver-based material obtained in Example 2 is better than that of the silver-based material obtained in Comparative Example 2. This is because Example 2 adopts a two-step reduction method, while Comparative Example 2 adopts a one-step reduction method. The one-step reduction method adopted in Comparative Example 2 fails to fully reduce the multi-component composite metal oxide silver composite powder. The presence of a small amount of silver oxide causes a significant decrease in the strength of the silver-based material and also reduces the electron emission ability of the silver-based material. Figure 4It can also be found that the silver-based materials obtained in Example 2 and Comparative Example 2 have good plasticity, indicating that the multi-metal composite oxide in the silver-based material prepared by chemical composite precipitation has better interface bonding with the silver matrix.
[0129] Figure 5 (a) is a microstructure photo of the silver-based material coarse material obtained after reduction in step 5 of Example 2 of the present invention and a photo of the material out of the furnace, and (b) is a microstructure photo of the silver-based material coarse material obtained after reduction in step 5 of Comparative Example 3 of the present invention and a photo of the material out of the furnace. The difference between Comparative Example 3 and Example 2 is that in Comparative Example 3, the material is not pressed into a rough material after vibration compaction, but is directly subjected to subsequent hot isostatic pressing sintering. Figure 5 It can be seen from (a) that the silver-based material coarse material prepared in Example 2 of the present invention has a uniform and dense structure, no obvious multi-component composite metal oxide agglomeration is found, and there are no obvious defects such as voids; after the silver-based material coarse material is fired, there is a small degree of necking. Figure 5 It can be seen from (b) that the silver-based material rough material obtained in Comparative Example 3 has a large number of defects and obvious voids; and after the silver-based material rough material is taken out of the furnace, it has severe necking, which makes subsequent processing difficult, reduces material utilization, and affects actual production efficiency. This shows that first pressing the multi-component composite metal oxide silver composite powder and then hot isostatic pressing sintering can improve the density of the silver-based material rough material and facilitate subsequent processing.
[0130] The properties of the silver-based materials prepared in various embodiments and comparative examples are shown in Table 1.
[0131] Table 1 Comparison of performance parameters of silver-based materials in various embodiments and comparative examples
[0132]
[0133] As can be seen from Table 1, the density, resistivity, hardness and ablation loss rate of the silver-based material prepared in Example 2 of the present invention are significantly better than those of the silver-based materials in Comparative Examples 1-3. Compared with Comparative Example 1, the ablation loss rate of the silver-based material obtained in Example 2 is significantly reduced, which is attributed to the fact that the multi-component composite metal oxide obtained in Example 2 is distributed and dispersed in the silver matrix, making the silver matrix emit electrons more stable and uniform. The various properties of the silver-based materials in Comparative Examples 2 and Comparative Examples 3 are more significantly reduced compared with those in Example 2, indicating that the effects of two-step reduction and pressing before hot isostatic pressing on the silver-based materials are more obvious, among which the silver-based material obtained in Comparative Example 3 without pressing before hot isostatic pressing has an extremely high ablation loss rate. This shows that chemical composite precipitation, two-step reduction and pressing before hot isostatic pressing play a key role in the preparation of silver-based materials, and can significantly improve the ablation resistance and service life of the final silver-based materials.
Claims
1. A method for preparing a silver-based material, characterized in that: The steps include: S1, adding silver nitrate, tin acetate, indium salt and zinc salt into water, stirring and mixing to obtain a metal salt solution; adding sodium hydroxide solution into the metal salt solution until the pH value of the metal salt solution reaches 9-11, thereby obtaining a suspension; S2, adding polyacrylamide to the suspension to perform flocculation precipitation treatment, and washing and drying the obtained precipitate to obtain a composite precipitate; S3, in a reducing atmosphere, heating the composite precipitate to 100-150° C., keeping the temperature for a first preset time, and then heating the composite precipitate to 250-300° C., keeping the temperature for a second preset time, to obtain a multi-component composite metal oxide silver composite powder; S4, hot isostatic pressing and sintering the multi-component composite metal oxide silver composite powder to obtain a silver-based material coarse material; S5, hot forging the silver-based material to obtain a silver-based material; S4 specifically includes: S41, compacting the multi-component composite metal oxide silver composite powder, and then pressing it into a rough material at a pressure of 200-300 MPa; S42, under a pressure of 50-100 MPa, the raw material is heated to 250-300°C for preheating, and then heated to 800-900°C for hot isostatic pressing sintering.
2. The method for preparing the silver-based material according to claim 1, characterized in that: In S1, the indium salt is indium nitrate, indium sulfate or indium trichloride, and the zinc salt is zinc nitrate, zinc sulfate or zinc chloride.
3. The method for preparing the silver-based material according to claim 1, characterized in that: In S1, the molar ratio of silver ions, tin ions, indium ions and zinc ions in the metal salt solution is 1: (0.071-0.077): (0.0038-0.0098): (0.019-0.030).
4. The method for preparing the silver-based material according to claim 1, characterized in that: In S2, the added amount of the polyacrylamide is 0.08%-0.1% of the sum of the mass of silver nitrate, tin acetate, indium salt and zinc salt.
5. The method for preparing the silver-based material according to claim 1, characterized in that: In S3, the first preset time is 1-2 hours, and the second preset time is 1-2 hours.
6. The method for preparing the silver-based material according to claim 1, characterized in that: S5 specifically includes: S51, in a reducing atmosphere, heating the silver-based material raw material to 500-700°C for preheating for 20-30 minutes, and then forging, with a forging amount of 10%-20% and a forging time of 20-30 seconds; S52, after forging, heat to 500-700℃ for preheating for 10-15min, and then forge, the forging amount is 10%-15%, and the forging time is 20-30s; S53, repeat S52 several times to obtain a silver-based material.
7. The silver-based material obtained by the preparation method according to any one of claims 1 to 6.
8. A cathode assembly, characterized in that: The cathode component is made of the silver-based material described in claim 7.
9. A plasma generator, characterized in that: Comprising the cathode assembly of claim 8.
Citation Information
Patent Citations
Method for preparing high-performance cathode material for plasma ignition
CN101497128A
Processing method of silver tin oxide electrical contact material containing additives
CN104498762A
Method for producing composite powders based on silver-tin oxide, the composite powders so produced, and the use of such powders to produce electrical contact materials by powder metallurgy techniques
US20010051102A1
Process for manufacture of silver-based composite powders for electrical contact materials and composite powders so produced
US20070228334A1
Method of Preparing Silver-Based Oxide Electrical Contact Materials with Fiber-like Arrangement
US20130266468A1
